Interactive E-learning environment for wireless chargers - Lee, Geraldyne Jia Yee (Nanyang Technological University, 2022)
This report focuses on developing an Interactive E-Learning Platform for students to learn more about wireless chargers. This project showcases the software development of an E-Learning website and the implementation of hardware components to build a wireless charging circuit. The whole project will enable students to learn about wireless charging and gain hands-on experience with building wireless charger circuits. With the help of Visual Studio and Arduino, the hardware and software components are integrated together. For developing the software part, HTML, CSS and JavaScript programming languages are used to create the E-Learning website. The website will help students to learn more about wireless charger content. As for the hardware part, it involves building a simple circuit that simulates how a wireless charger works. This will ensure that any beginner who does not know much about circuits can also build the hardware component easily.